Answer:
I already did
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
Add all the numbers together and divide by the amount of numbers
6+9+3+8+9+3+4= 42
42/7 = 6
Answer:
Fill in the blanks to make the following statements true. Also named the property used.
a. (-5) + (-4) = ___ + (-5),
b. 4 + __ = 4,
c. - 53 + ___ = - 53,
d. 4 + [(-5) + (7)] = [4 + (7)] + ___,
e. 25 + [(-50) + 5 ] = (25 + 5) + ___,
f. (-4) + ___ = -4,
g. 4 + (-4) = ___,
h. 5 + ___ = 0 ,
Step-by-step explanation:
Fill in the blanks to make the following statements true. Also named the property used.
a. (-5) + (-4) = ___ + (-5),
b. 4 + __ = 4,
c. - 53 + ___ = - 53,
d. 4 + [(-5) + (7)] = [4 + (7)] + ___,
e. 25 + [(-50) + 5 ] = (25 + 5) + ___,
f. (-4) + ___ = -4,
g. 4 + (-4) = ___,
h. 5 + ___ = 0 ,
Answer:
x=0.2
Step-by-step explanation:
The graph is not proportional because it doesn’t go though the origin aka (0,0)